2020
DOI: 10.3390/en13061495
|View full text |Cite
|
Sign up to set email alerts
|

Energy Value of Yield and Biomass Quality of Poplar Grown in Two Consecutive 4-Year Harvest Rotations in the North-East of Poland

Abstract: Bioenergy accounts for 61.7% of all renewable energy sources, with solid fuels accounting for 43% of this amount. Poplar plantations can deliver woody biomass for energy purposes. A field experiment with poplar was located in the north-east of Poland on good quality soil formed from medium loam. The study aimed to determine the yield, the energy value of the yield and the thermophysical properties and elemental composition of the biomass of four poplar clones harvested in two consecutive 4-year harvest rotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…30% of the country area) and the amount of wood acquired annually (over 40 million m 3 ) [8], wood processing industry waste and post-felling biomass, i.e., branches and twigs left over after tree felling, is the dominating source of woody biomass. Plantations of woody crops grown as short rotation coppice (SRC) are another source of woody biomass and include mainly willow and poplar [9][10][11][12][13]. The area of poplar and willow cultivation in the SRC system in Poland is estimated at approx.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30% of the country area) and the amount of wood acquired annually (over 40 million m 3 ) [8], wood processing industry waste and post-felling biomass, i.e., branches and twigs left over after tree felling, is the dominating source of woody biomass. Plantations of woody crops grown as short rotation coppice (SRC) are another source of woody biomass and include mainly willow and poplar [9][10][11][12][13]. The area of poplar and willow cultivation in the SRC system in Poland is estimated at approx.…”
Section: Introductionmentioning
confidence: 99%
“…Significant differences in bark and ash content were found in initial breeding experiments on many willow genotypes of many species in the USA [29,30]. Later studies also revealed great differences between 18 willow genotypes with respect to polysaccharides and ash and considerable genotype interactions with the environment for some characteristics [11]. Therefore, both genetic factors and environmental and agrotechnical conditions have a significant effect on the composition and quality of biomass [28,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The application of supercritical fluid and utilization of renewable substrate from perennial industrial crops, including those grown on marginal land using a short-rotation coppice system presented in this publication, could be an important contribution to the bioeconomy and circular economy [ 36 , 37 ]. Information on this complex topic is scarce in the scientific literature, and the majority of data are limited to the production of bioenergy from this non-food lignocellulosic substrate [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interest in bioenergy has increased globally (Griffiths et al, 2019; Qin et al, 2018; Stolarski et al, 2020; Zhang et al, 2020). In 2019, the European Union (EU) updated its energy policy framework to include a transition from fossil fuels towards cleaner energy and deliver on the EU's Paris Agreement commitments for reducing greenhouse gas (GHG) emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Another promising biomass source includes short rotation woody crop (SRWC) systems, based on short, clear‐felling cycles (generally between 1 and 15 years) utilizing genetically superior planting material, and often relying on coppice regeneration (Griffiths et al, 2019; Dickmann, 2006). The production of biomass as feedstock for energy generation and industrial processes from SRWC plantations is still being developed in many countries in Europe (Afas et al, 2008; Dillen et al, 2013; Njakou Djomo et al, 2015; Stolarski et al, 2020; Verlinden et al, 2015), the USA and Canada (Clifton‐Brown et al, 2019; Ghezehei et al, 2020; Zalesny & Headlee, 2015). Biomass is generally presumed to be carbon neutral, given that emissions from biomass combustion are compensated by plant regrowth (Ragauskas et al, 2006; Yan, 2018; Zeman & Keith, 2008).…”
Section: Introductionmentioning
confidence: 99%